The Influence of Artificial Intelligence Marketing and Generative Storytelling on Brand Engagement in the Culinary Industry in West Java - Ajub Ajulian ZM; Enda Wista Sinuraya (West Science Interdisciplinary Studies, 2025)
This study investigates the influence of Artificial Intelligence (AI) marketing and creative storytelling on brand engagement in the culinary industry in West Java. Using a quantitative approach, data were collected from 150 respondents through a structured Likert-scale questionnaire and analyzed using SPSS Version 25. Descriptive statistics, reliability and validity tests, and multiple linear regression analysis were employed to examine the relationships between variables. The results indicate that both AI marketing and creative storytelling have a significant positive effect on brand engagement, with creative storytelling showing a slightly stronger influence. Combined, these factors explain 38.2% of the variance in brand engagement. The study highlights the importance of integrating AI-driven marketing strategies with compelling narratives to strengthen consumer interaction and loyalty, providing practical guidance for culinary businesses seeking competitive advantage in West Java.